Prospecção de leveduras de compostagem tolerantes à disruptores endócrinos inorgânicos - Trama, Bianca [UNIFESP] (2013)
The input of inorganic endocrine disruptors of anthropogenic origin in the environment has been pointed out by scientists, nongovernmental agencies and government as an imminent public health problem. Among the innovative solutions for contaminated water treatment is the use of biological materials like living or dead microorganisms as biosorbent. Yeasts exhibit the ability to adapt to extreme condition such as temperature, pH and levels of organic and inorganic contaminants that make them a potential material to be used as biosorbent for contaminated environment application. The aim of this project was to access the tolerance of several yeast strains isolated from the São Paulo Zoo composting unit to the presence of inorganic endocrine disruptors such as Pb2+ and Mn2+. Four yeast strains (BY4742, PE-2, CAT-1 and BG-1) were employed as source of comparison for tolarence and sorption ability. As a result we found one yeast with high potencial for Pb biosorption and nine isolates with high tolerance to Mn which can be utilized in sorption process.